Effect of rice flour binder concentration on the characteristics of peanut shell charcoal briquettes as an alternative fuel - Ahmad Akromul Huda; Syarif Hidayatullah; Suteja Suteja (Jurnal Agrotek Ummat, 2026)
The use of peanut shell waste as briquettes is a renewable energy alternative with the potential to improve the quality of solid fuel. This study aims to analyze the effect of rice flour binder concentration on the quality of peanut shell charcoal briquettes based on quality parameters and their compliance with SNI standards. The method used was an experiment with a Completely Randomized Design (CRD) at binder concentrations of 10%, 15%, 20%, and 25%. The tested parameters included calorific value, moisture content, ash content, and burning rate. The results showed that an increase in binder concentration reduced the calorific value from 5,450 cal/g to 4,676 cal/g, and increased the moisture content to 7.9% and the ash content to 8.4%. All treatments met the SNI moisture content standard (<8%), but the ash content only met the standard up to a 20% concentration. The combustion rate decreased from 0.0042 g/s to 0.0031 g/s, while the burning time increased from 50.7 minutes to 68.8 minutes. Overall, the best briquette quality was obtained at a binder concentration of 10–20% because it met SNI standards, had a high calorific value, low moisture and ash content, and stable combustion. Therefore, controlling the binder concentration is crucial for producing briquettes of optimal quality.